Evaluation of the efficacy of surgical treatment of cataracts in patients with neovascular age-related macular degeneration - A. Zh. Fursova; E. I. Dmitrieva; M. A. Vasil’eva; A. S. Derbeneva; Yu. A. Karlash; I. F. Nikulich; A. A. Atamanenko; M. S. Tarasov (Российский офтальмологический журнал, 2024)
Purpose. To study of the effectiveness of cataract surgery based on the results of a comprehensive evaluation, including the patient's opinion about the state of visual functions, when assessed using a questionnaire before and after surgery.Material and methods. 117 patients (117 eyes) diagnosed with nAMD and cataract (LOCS I — 56 patients, 47.9 %; LOCS II — 57 patients, 48.7 %, LOCS III — 4 patients, 3.4 %), mean age 76.2 ± 5.7 years were included in the study. All patients received angiogenesis inhibitor therapy (aflibercept 2 mg), in Treat&Extend regimen. Cataract surgery was performed if disease activity is controlled. A questionnaire including 10 questions was developed to interview patients, 9 of which were assessed before, 1 and 6 months after cataract surgery, and a 10th question on patient satisfaction with the results of surgery — 1 and 6 months after cataract surgery.Results. There was a significant improvement in functional (increase in BCVA by 0.31 units from the baseline) and anatomical parameters (significant decrease in CRT, height of neuro- and pigment epithelium detachment), as well as in patients' assessment of vision-related quality of life. The most compromised aspect before surgery was the ability to read text in newspapers, books, and magazines. After surgery there was a significant improvement of the indicators characterizing the patient's adaptation to navigation and outside activities. There were minimal changes in central vision loss and metamorphopsia as assessed by patients (on average, by 0.02 b. and 1.21 b.). 99 patients (84.0 %) reported satisfaction with the results of the surgery. The strongest correlations (r = 0.94 and 0.81, p < 0.05) characterized the relationship between patients' evaluation of the effect of surgery and the presence of central vision spotting/loss of central vision, double vision.Conclusion. The results of surgery significantly contribute to the patient's assessment of his/her daily activities requiring clearer vision, primarily in the middle and far distances. Cataract surgery does not worsen the course of nAMD and, on the contrary, cataract surgery and continuation of antiangiogenic therapy contribute to a significant improvement in BCVA and anatomical improvement.